2019
DOI: 10.3390/ijms20082027
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Attenuates Cadmium-Induced Nephrotoxicity via Inhibition of Oxidative Stress, Apoptosis, Inflammation and Fibrosis

Abstract: The present investigation was executed to reveal the protective mechanism of rosmarinic acid (RA) against cadmium (Cd)-induced nephrotoxicity. RA exhibited a concentration-dependent anti-apoptotic effect against CdCl2 in isolated mouse proximal tubular epithelial cells. Cd treatment significantly (p < 0.01) imparted oxidative stress to the renal cells via excessive ROS production, triggering NO level, NADPH oxidase activation, and impairment of cellular redox defense system. Cd-mediated oxidative stress sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 64 publications
4
84
0
Order By: Relevance
“…[ 45 ] Among these agents is RA, which has attracted wide consideration because of its hepatorenal protective potentials against metal‐induced toxicity. [ 46 ] Rosemary extracts posses many biological activities including antimicrobial, [ 47 ] antimutagenic, [ 48 ] antihyperglycemic, [ 49 ] and antioxidant actions. [ 50,51 ] Our finding showed that RA significantly upregulated Nrf2 gene to attenuate the hepatorenal oxidative damage induced by chromium.…”
Section: Discussionmentioning
confidence: 99%
“…[ 45 ] Among these agents is RA, which has attracted wide consideration because of its hepatorenal protective potentials against metal‐induced toxicity. [ 46 ] Rosemary extracts posses many biological activities including antimicrobial, [ 47 ] antimutagenic, [ 48 ] antihyperglycemic, [ 49 ] and antioxidant actions. [ 50,51 ] Our finding showed that RA significantly upregulated Nrf2 gene to attenuate the hepatorenal oxidative damage induced by chromium.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a notable increase in LPO and a remarkable decrease in TTM were found in the cadmium group, indicating the induction of oxidative stress in renal tissue. In this regard, renal oxidative injury induced by cadmium has been reported in several studies (8,22,23). LPO is a radical reaction that leads to the destruction of polyunsaturated fatty acids in lipid membranes and cell death (24).…”
Section: Discussionmentioning
confidence: 99%
“…For example, rosmarinic acid small molecule mainly forms 9 hydrogen bonds with GLN-102, PRO-100, SER-99, TYR-115 and ARG-103 residues on TNF. Rosmarinic acid, which is considered one of the most important polyphenols, has several pharmacological effects: anti-oxidant, inhibition of oxidative stress, anti-inflammatory, anti-cancer and immunomodulatory [77,78]. Besides, it has been reported that rosmarinic acid may inhibit the expression of NF-κB promoter-related genes.…”
Section: Discussionmentioning
confidence: 99%